Jean Donneau de Visé et la querelle de Sophonisbe. Écrits contre l'abbé d'Aubignac Édition critique par Bernard J. Bourque - Bourque, Bernard J. 1953- (Biblio 17, 2014)
This work is the first critical edition of the three Défenses by Jean Donneau de Visé (1638-1710), in which the author ardently defends Pierre Corneille against the four dissertations published by Abbé d'Aubignac. The third of these Défenses (Défense d'Œdipe) is largely unknown and has never before been published since the original edition. The critical edition makes the three Défenses more easily accessible to scholars and students of French seventeenth-century literature and provides insight into Donneau de Visé's role in the Quarrel of Sophonisbe